ANALYSIS OF THE CORRELATIONAL-INTEGRATIVE RELATIONSHIP BETWEEN FINANCIAL ANALYSIS USING FINANCIAL RATIOS AND CREDIT RISKS IN THE IRAQI BANKING SECTOR - Layla Abed Jasim (Scholar Express Journals, 2025)
Banks serve as an intermediary linking two essential parties: savers who have surplus funds and investors who require financing. Through their role in attracting both local and foreign savings and accepting them in the form of deposits with various maturities, banks utilize these savings to provide credit facilities and loans. This utilization has a positive impact on the national economy, as it funds projects that contribute to increasing the country's production capacity. However, this process involves several risks that credit decision-makers must consider. To mitigate these risks, banks have sought to use modern financial analysis as a crucial tool for evaluating the success or failure of credit policies. This is done by transforming the data available in financial statements into meaningful information that can be used as a basis for making decisions aimed at achieving financial management goals, maximizing enterprise value, and increasing profits.
Keywords: Financial analysis; financial analysis indicators; credit in Iraq